Climate justice beliefs related to climate action and policy support around the world - Ogunbode, Charles A.; Doran, Rouven; Ayanian, Arin H.; Park, Joonha; Utsugi, Akira; Van den Broek, Karlijn; Ghorayeb, Jihane; Aquino, Sibele D.; Lins, Samuel; Aruta, John J. B. R.; Reyes, Marc E. S.; Zick, Andreas; et al. (Nature climate change, 2024)
Climate justice is increasingly prominent in climate change communication and advocacy but little is known about public understanding of the concept or how widely it resonates with different groups. In our global survey of 5,627 adults in 11 countries spanning the global north and south, most participants (66.2%) had never heard of climate justice. Nonetheless, endorsement of climate justice beliefs was widespread (for example, acknowledging the disproportionate impact of climate change on poor people and the underpinning roles of capitalism and colonialism in the climate crisis). Climate justice beliefs were also associated with various indices of climate action and policy support. These associations tended to be stronger in countries with high GHG emissions and where social inequality is also more politically salient. The results highlight the value of climate justice as a motive for climate action across diverse geographical contexts.